Early Childhood Tahfidz Learning Using the Developmentally Appropriate Practice (DAP) Approach to Improve Qur'an Reading Skills - Mila Syahlaena; Saefuddin (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Learning tahfidz in early childhood not only requires the ability to memorize Qur'anic verses, but also requires strengthening reading skills as a basis for more precise and quality memorization. In practice, some tahfidz learning is still repetitive and academic so that it is not in accordance with the characteristics of child development. The Developmentally Appropriate Practice (DAP) approach offers child-friendly learning strategies through play activities, hands-on experiences, and stimuli tailored to the child's cognitive, language, and social-emotional developmental stages. This study aims to describe the application of DAP-based tahfidz learning and find out its improvement in children's Qur'an reading skills. The method used is descriptive qualitative. The subject of the study is the children of Tahfidz Kindergarten MQA Banteran, while the object of the research includes the tahfidz learning process and the development of the ability to read the Qur'an. Data was collected through observation of learning activities, interviews with kindergarten principals, teachers, and documentation. The results of the study show that the application of DAP through game-based hijaiyah letter recognition activities, muroja'ah with songs, the use of concrete media, and the habit of reading gradually can improve children's ability to pronounce letters, improve letter meaning, and read short verses more fluently. This model also fosters children's sense of joy and motivation in tahfidz.